2013
DOI: 10.5588/pha.13.0019
|View full text |Cite
|
Sign up to set email alerts
|

Standard case management of asthma in Sudan: a pilot project

Abstract: The results of standard case management of asthma were encouraging; however, a high proportion of patients did not return for long-term management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…The importance of recording contact information should be emphasised to patient registration clerks. Another study from Sudan, focusing on severe cases, revealed a loss to follow-up of 56%, 9 and another from Benin reported 36% loss to follow-up. 10 These findings suggest the need for more effective tracing strategies for asthma patients on follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…The importance of recording contact information should be emphasised to patient registration clerks. Another study from Sudan, focusing on severe cases, revealed a loss to follow-up of 56%, 9 and another from Benin reported 36% loss to follow-up. 10 These findings suggest the need for more effective tracing strategies for asthma patients on follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…While asthma is a concern for the Ministry of Health in Sudan, it is not listed as a public health priority. In the public health sector there are very few peak flow meters (which measure a person's ability to breathe out air) for diagnosis, few drugs available, and few staff trained in asthma management 12 . Many health professionals working in both the public and private sectors are not trained in tackling chronic asthma or long-term management of the disease 5 .…”
Section: Asthma In Sudan: a Growing Problemmentioning
confidence: 99%
“…The Union implemented asthma pilot projects in Benin [11], China (Huaiyuan County) [12], El Salvador [13] and Sudan [14]. These projects found that inhaled corticosteroids were not available in any of these sites in the public sector and that asthma was greatly underdiagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…GAN Phase I is a development from ISAAC ( particularly Phases One [17][18][19][20][21] and Three [22][23][24]), and The Union [11,12,14,25]. GAN Phase I has extended its surveillance to include adults, for whom there are limited global data, and to assess asthma management, which is commonly suboptimal in settings with limited access to quality-assured essential asthma medicines.…”
Section: Introductionmentioning
confidence: 99%